The Dopamine Hypothesis of Drug Addiction and Its Potential Therapeutic Value - Diana, Marco (Frontiers in Psychiatry, 2011)
Dopamine (DA) transmission is deeply affected by drugs of abuse, and alterations in DA function are involved in various phases of drug addiction and potentially exploitable therapeutically. In particular, basic studies have documented a reduction in the electrophysiological activity of DA neurons in alcohol, opiate, cannabinoid and other drug-dependent rats. Further, DA release in the Nacc is decreased in virtually all drug-dependent rodents. In parallel, these studies are supported by increments in intracranial self stimulation (ICSS) thresholds during withdrawal from alcohol, nicotine, opiates, and other drugs of abuse, thereby suggesting a hypofunction of the neural substrate of ICSS. Accordingly, morphological evaluations fed into realistic computational analysis of the Medium Spiny Neuron (MSN) of the Nucleus accumbens (Nacc), post-synaptic counterpart of DA terminals, show profound changes in structure and function of the entire mesolimbic system. In line with these findings, human imaging studies have shown a reduction of dopamine receptors accompanied by a lesser release of endogenous DA in the ventral striatum of cocaine, heroin and alcohol-dependent subjects, thereby offering visual proof of the ‘dopamine-impoverished’ addicted human brain. The reduction in physiological activity of the DA system leads to the idea that an increment in its activity, to restore pre-drug levels, may yield significant clinical improvements (reduction of craving, relapse and drug-seeking/taking). In theory, it may be achieved pharmacologically and/or with novel interventions such as Transcranial Magnetic Stimulation (TMS). Its anatomo-physiological rationale as a possible therapeutic aid in alcoholics and other addicts will be described and proposed as a theoretical framework to be subjected to experimental testing in human addicts.